A rare case of cardiac tumor: Malignant fibrous histiocytoma - Sarı, Hasan; Tatar, Sefa; Alsancak, Yakup (Journal of Surgery and Medicine, 2020)
Cardiac tumors are generally benign; however, they can rarely be malignant. Malignant fibrous histiocytoma is a type of sarcoma. Cardiac malignant fibrous histiocytomas are clinically and histologically confused with atrial myxomas. In this case report, we present a patient who was administered to the hospital with non-specific complaints, determined to have an intracardiac mass and subsequently diagnosed with malignant fibrous histiocytoma, which shortly recurred in the form of intracardiac masses after postoperative chemotherapy.